Dampak Covid-19 Pada Rantai Pasokan dan Praktik Manajemen Sumber Daya Manusia dan Pemasaran Di Masa Depan - nurul haeriyah,; Wahyudi, Wahyudi (Study of Scientific and Behavioral Management, 2022)
The increasing prevalence of COVID-19 has severe implications on the well-being of most organizations and professionals especially in the areas of human resource management and marketing. This study focuses on determining the impact of COVID-19 on different human resource practices and future marketing. It was determined that the dynamics of work had greatly changed from the traditional way of working from an organizational place to working remotely at home. As a result, marketing has also shifted to different online platforms because physical contact with customers is currently prohibited to maintain social distance, one of the ways to prevent the corona virus. This change has been associated with different negative implications and some positives as some professionals find it more flexible and comfortable to work remotely. To cope with the changing times of today, organizations need to adapt and adopt new emerging technologies to work remotely and consequently implement strategic policies and procedures to maintain a steady flow. Keywords: Human Resource Management, supply chain management, Covid-19, Marketing, SARS-CoV-2